Rupture of the recurrent thoracic intramedullary spinal cord cavernoma - Galih Indra Permana; Eko Agus Subagio; Muhammad Faris; Abdul Hafid Bajamal (Indoscholar, 2021)
The intramedullary spinal cord cavernoma is a rare vascular disease that occur within spinal cord or intramedullary and account for about 5%-12% of all pathology in the spinal vascular disease. We report a clinical progression of disease and evolution of the haemorrhage every years until patient underwent surgical procedure. A 63-years old male with progressive weakness of the lower extremity since 1 month before admission, worse in the left side He also complained loss of sensation at the level of the T4 and below it. Patient suffer three times rebleeding before underwent surgery. MR imaging showing intramedullary spinal cord cavernoma and a histology examination exhibited the characteristics of a cavernoma. Intramedullary spinal cord cavernoma is a rare disease that should be treated before rebleeding occur and enlargement of the lesion. Postoperative neurological function in intramedullary spinal cord cavernoma patient is determined by the preoperative neurological status.